UPAYA GURU BK DALAM MENINGKATKAN KEMAMPUAN KOMUNIKASI INTERPERSONAL SISWA DI MAL UIN SU MEDAN - Ira Suryani (Al-Irsyad: Jurnal Pendidikan dan Konseling, 2018)
This study aims to get a clear picture of the implementation of group guidance services, interpersonal communication of students, the implementation of group guidance services can improve student interpersonal communication at MAL UIN SU Medan. As for the informants in this study were the supervisors and students of MAL UIN SU Medan. This type of research is qualitative research that is research that seeks to find facts and reduce research findings. The results of the study can be stated that the implementation of group guidance services at MAL UIN SU Medan was carried out outside of school hours and carried out in the counseling and counseling room, meaning that students carry out group guidance services during out-of-school hours so as not to interfere with student learning activities in the classroom. This is done because there are no hours for guidance and counseling. Interpersonal communication of students at MAL UIN SU Medan as a whole is quite good. This is evidenced by students who have good communication with friends and teachers. And the school, especially the supervising teacher, strives to improve students' interpersonal communication. The implementation of group guidance services in improving student interpersonal communication is well implemented. The meaning of implementing group guidance services can improve student interpersonal communication. After giving group guidance services to students, students are increasingly enthusiastic about being good with fellow peers and communicating well with teachers when in class.Keywords: Efforts of Bk Teachers in Improving Student Interpersonal Communication at MAL UIN SU Medan